Ennis Franciscan Friary, cloister, base - O'Donovan, Danielle; O'Donoghue, Aisling (My University, 2008)
Cloister base, moulding from top comprises: roll, bell, fillet, roll, chamfer running into plinth.
Cloister
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Cloisters (Architecture); Late Medieval; roll moldings; plinth; fillets (moldings)